Aplicações de estratégias fotoquímicas para a síntese de moléculas com potencial atividade biológica: funcionalização de nitronas e β-glicosil β-lactamas - Tordato, Éverton Alves (2024)
Nitrones and β-lactams are important classes of compounds due to their great relevance to the synthetic and medicinal organic chemistry community. Nitrones are 1,3-dipoles widely used in cycloaddition reactions for the synthesis of natural products (including β-lactams) and heterocycles, as well as electrophilic partners in addition reactions. β-lactams, in addition to their recognized antibacterial activity, also have other biological activities, and can be used as advanced synthons in the production of other valuable compounds such as β amino acids and peptides. In recent years, our research group has been working, among other topics, with the functionalization of compounds via photochemical route, from the addition of carbamoyl or alkyl radicals. In this sense, we envision the possibility of exploring the addition of radicals to nitrones and using them as starting materials for the preparation of electrophilic β-lactams to be subjected to photochemical functionalization. In the first work, a large structural diversity of nitrones were functionalized from the addition of carbamoyl radicals, originating from the oxidation of the radical precursor 4-carbamoyl 1,4-dihydropyridines using the photocatalyst 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN), under continuous flow regime. It was possible to obtain 49 examples of α-(N-hydroxy)amino amides, a nucleus present in several bioactive compounds, with yields of 26 to 95% and diastereoisomeric ratios (rd) of 1:1 to 20:1, from the formation of a C(sp2)-C(sp3) bond. It is worth mentioning that the batch reaction lasted 15 h and under continuous flow regime it was completed in only 30 min. In the second work, the N-phenyl 3 exo-methylene β-glycosyl β-lactam nucleus, synthesized from a variant of the Kinugasa reaction, using N-phenyl α-glycosyl nitrones and propargyl alcohol, was functionalized from the addition of alkyl radicals generated via photoinduction of EDA complex between Hantzsch ester (HE) and N-(acyloxy)phthalimides. It was possible to obtain 19 examples with yield of 37 to 66% and excellent cis/trans rd, mostly 20:1, in only 2 h of reaction providing the expansion of the chemical space of this important class of heterocycle, from the formation of a diastereoselective C(sp3)-C(sp3) bond. The absolute cis configuration of the functionalized β-lactam nucleus was unequivocally determined from the X-ray diffraction analysis of a single crystal. It was possible to obtain evidence that one of the pathways involved in the formation of the stereogenic center at C3 occurs via diastereoselective hydrogen atom transfer, probably by HE. This could be observed from the high-resolution mass spectrometry analysis, where it was possible to determine the mass of the radical-radical coupling product between the radical intermediate and TEMPO. In short, it was possible to synthesize dozens of novel molecules using important classes of compounds as substrates from the addition of photogenerated radicals of biorelevant compounds such as amino acids, drugs, monosaccharides and other natural products under mild, scalable and fast reaction conditions.